Clinical and Psychopathological Features of Mental Disorders in Patients with Poisoning by Hypotensive and Antiarrhythmic Drugs as a Result of Suicidal Acts - T. I. Dikaya; K. K. Ilyashenko; G. N. Sukhodolova; O. V. Zubareva; M. M. Potskhveriya (Неотложная медицинская помощь, 2024)
BACKGROUND. Among the forms of suicidal behavior, self-poisoning is the most common one, often occurring as a result of taking various medications, the second place among them is occupied by antihypertensive and antiarrhythmic drugs. Studying the structure of mental disorders in suicide victims with poisoning by these drugs is necessary to prevent repeated suicidal acts.   AIM OF STUDY. To study the clinical and psychopathological features of mental disorders in patients with acute poisoning by hypotensive and antiarrhythmic drugs as a result of suicidal acts.   MATERIAL AND METHODS. The results of a psychopathological study were analyzed in 122 patients (age 15–93) with antihypertensive and antiarthymic drugs poisoning as the suicidal attempt.   RESULTS. In the structure of mental disorders in patients with suicidal poisoning by hypotensive and antiarrhythmic drugs, anxiety-depressive reactions associated with stress prevailed (F43.20–43.25) — 65.6 %. Endogenous mental pathology was detected in 19.7 % of patients, of which endogenous depression (F32–F34) — in 13.1 %, depressive — delusional states with schizophrenia (F20) — in 6.6 %. Organic personality, affective psychotic and delusional disorders (F06–F07) were diagnosed in 14.7 % of patients. In 45.9 % of patients, acute poisoning occurred against the background of comorbid somatic pathology, in 87.5 % of them — of cardiovascular genesis. Typological variants of early postsuicidal states in the studied contingent of patients are as follows: critical type of postsuicide (54.9 %), manipulative (16.4 %), fixed (14.8 %), unspecified (13.9 %); their significance for assessing repeated suicidal risk was determined.   CONCLUSION. The findings of the study complement the understanding of the patterns of suicidal behavior in patients with self-poisoning, which will improve approaches to the prevention of suicide through drug poisoning.